The travesty of jaffna in jean arasanayagam’s poems - Sivapalan, C.C.A.; Tharuni, S. (University of Jaffna, 2012)
Jaffna is one of the native places of the Tamil ethnic community in Sri Lanka. Jaffna has its own Tamil culture, tradition and literature. Compared to the Tamil writings, the writings emerged about Jaffna in English are very limited. Jean Arasanayagm is the only prominent writer from the main stream narrative of Sri Lanka, who has offered prominence to Jaffna and the ethnic strife of Sri Lanka in her literary works. While reading her literary works of Jean Arasanayagam the reader can perceive an image of Jaffna. The researcher of this paper would like to focus on the manner in which traditions, rituals and customs of the Hindu society of Jaffna are viewed through the eyes of a foreigner, a Burgher, Jean Arasanayagam, whose familiarity with Jaffna is under criticism. The author of a particular literary work is expected to be the resident of the area which is dealt within the work, in order to present authentic data with first-hand experience. Arasanayagam’s knowledge about Jaffna is not from her own experience but from the mouth of her husband who was born and brought up in Jaffna. D.C.R.A. Goonetilleke compares the works of Arasanayagam with that of Aiyathurai Santhan, a writer from Jaffna and states “Whereas Arasanayagam is not resident in Jaffna, A.Santhan is, and this is partly why he is better able to render present-day life in the North.” With the light of the statement by Goonetilleke, this paper attempts to explore whether the portrayal of Jaffna in the poems of Arasanayagam has the qualities or values that Jaffna should have or the portrayal is a travesty. Even though there is a wide range of references of Jaffna in the novel, short stories and poems of Arasanayagam the concern of this paper is restricted to the poems, especially to the collection, “The Landscape of Retrievals”.
Keywords: Authentic data; Perceive; Portrayal; Travesty